Sejarah Sosial Talak di Depan Pengadilan Agama dalam Undang-Undang Perkawinan di Indonesia - Muhammad Jazil Rifqi (AL-HUKAMA': The Indonesian Journal of Islamic Family Law, 2021)
Article 39 paragraph (1) of Law Number 1 of 1974 on Marriage and Article 115 of the Compilation of Islamic Law states that divorce must be carried out before the court. Of course, the existence of these regulations cannot be separated from the socio-historical aspects of the promulgation of these regulations. This article, which examines the practice of talak from the colonial period to independence, concludes that first, since the Dutch colonial era until Indonesia's independence, talak has been practiced without involving the state apparatus, but that the incident must be recorded. Law Number 22 of 1946 concerning the Registration of Marriage, Divorce and Reconciliation was then promulgated for Java and Madura, enacted in Sumatra in 1949 and comprehensively implemented in the territory of the Republic of Indonesia in 1954. Second, there was an acculturation of the recording of divorce and the trial of divorce came into effect when the law Marriage is promulgated.